A systematic review of known interventions for the treatment of chronic nonhypovolaemic hypotonic hyponatraemia and a meta‐analysis of the vaptans. (27th March 2017) - Bhandari, Sunil; Peri, Alessandro; Cranston, Iain; McCool, Rachael; Shaw, Alison; Glanville, Julie; Petrakova, Larisa; O'Reilly, Karl
Abstract: International and national guidelines on the treatment of chronic nonhypovolaemic hypotonic hyponatraemia differ; therefore, we have undertaken this systematic review and meta‐analysis to investigate the efficacy and safety of interventions for the treatment of chronic nonhypovolaemic hypotonic hyponatraemia. Following registration of the review protocol with PROSPERO, systematic literature searches were conducted to identify randomized and quasi‐randomized controlled trials assessing any degree of fluid restriction or any drug treatment with the aim of increasing serum sodium concentration in patients with chronic nonhypovolaemic hypotonic hyponatraemia. Where appropriate, outcome data were synthesized in a meta‐analysis. A total of 45 716 bibliographic records were identified from the searches and 18 trials (assessing conivaptan, lixivaptan, tolvaptan and satavaptan) met the eligibility criteria. Results suggest that all four vasopressin receptor agonists ("vaptans") significantly improve serum sodium concentration. Lixivaptan, satavaptan and tolvaptan were associated with greater rates of response versus placebo. There was no evidence of a difference between each of the vaptans compared with placebo for mortality, discontinuation and rates of hypernatraemia. No RCT evidence of treatments other than the vaptans for hyponatraemia such as oral urea, salt tablets, mannitol, loop diuretics demeclocycline or lithium was identified. Vaptans demonstrated superiority over placebo for outcomes relating to serum sodium correction. Few trials documented the potential benefit of vaptans on change in health‐related quality of life as a result of treatment. There was also a lack of high‐quality RCT evidence on the comparative efficacy of the vaptans and other treatment strategies for the treatment of chronic nonhypovolaemic hypotonic hyponatraemia.